STUDY ON THE ANTHROPOMETRIC PROFILE ON 5 EDARG ht TASLIPUP TECHNOLOGICAL HIGH SCHOOL "ELENA DOAMNA" DOLHASCA - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
During the course of the research I noticed that the motor activity is unitary, conscious, based on anticipation and supported by a consistent motivation. It is a complex phenomenon, of great amplitude that in the most frequent situations bears the "mark" of the individual's personality. The development of motor skills is closely related to the other advances in intellectual and socio-affective development. However, it is known and accepted that each child develops at his / her own pace, which is observed by comparing the students from the two classes who participated in the experiment proposed by me.